2022
DOI: 10.1108/ijwbr-05-2021-0028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atmosphere on emotions and consumer behaviour at wineries

Abstract: Purpose The aim of this study is to investigate the influence of atmosphere on consumer emotions and wine purchasing behaviours to assist winery management in the development and communication of a strong positioning strategy. Studies in retail have indicated the importance of atmosphere in relation to consumer emotions and behaviours. Until now, limited evidence has existed on how the three dimensions of atmosphere may influence consumers visiting wineries. Design/methodology/approach The study consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…In Quadri-Felitti and Fiore's [44] study, the authors revealed the crucial importance of the aesthetic dimension in visitors' satisfaction and loyalty and the moderate effect of the educational dimension in memorability and satisfaction. Sassenberg et al [43] also pointed at the outstanding importance of the natural environment (besides live music and social interaction, i.e., immaterial culture elements) to visitors' positive emotional well-being in a winery experience, corroborating other studies showing the relevance of natural and cultural resources. Cruz-Ruiz et al [45] present a model that comprises the elements that should be considered in a wine route or itinerary design, based on a literature review and on visitors, winemakers and stakeholders' perspectives from a wine destination in Spain.…”
Section: Experience Economy In Rural and Food And Wine Tourismsupporting
confidence: 52%
See 1 more Smart Citation
“…In Quadri-Felitti and Fiore's [44] study, the authors revealed the crucial importance of the aesthetic dimension in visitors' satisfaction and loyalty and the moderate effect of the educational dimension in memorability and satisfaction. Sassenberg et al [43] also pointed at the outstanding importance of the natural environment (besides live music and social interaction, i.e., immaterial culture elements) to visitors' positive emotional well-being in a winery experience, corroborating other studies showing the relevance of natural and cultural resources. Cruz-Ruiz et al [45] present a model that comprises the elements that should be considered in a wine route or itinerary design, based on a literature review and on visitors, winemakers and stakeholders' perspectives from a wine destination in Spain.…”
Section: Experience Economy In Rural and Food And Wine Tourismsupporting
confidence: 52%
“…Indeed, the experience context contributes to add unique value to the tourist experience, since natural (e.g., vineyards landscape) and cultural elements (e.g., traditions and local lifestyles) of the destination are also an integrative part of multisensory food and wine experiences [35,39]. Furthermore, Sassenberg et al [43] noted that the physical environment influenced visitors' emotions positively in wine tourism, stressing the importance of natural settings (e.g., gardens) in winery experiences. Indeed, the adoption of a holistic perspective of food and wine experiences contributes to visitors' satisfaction and loyalty, as pointed out in this and other studies.…”
Section: Experience Economy In Rural and Food And Wine Tourismmentioning
confidence: 99%
“…The concept of “sensescape” (Quintal et al , 2015) in wine tourism needs further scrutiny in relation to experiences. Music is a powerful stimulus that is formative in wine tourism experiences (De Luca et al , 2019; Sassenberg et al , 2022). Several studies have studied the effect of colour, texture, temperature, aroma, flavours and wine glass shape on wine-tasting experiences (Heatherly et al , 2019; Ross et al , 2012; Wan et al , 2015).…”
Section: Agenda For Future Researchmentioning
confidence: 99%
“…Music has positive and negative influences on consumers’ emotions within the environment in which they complete their purchases. Moreover, it is able to extend consumers’ in-store visits, promoting a name, brand, and experience that customers experiment with during their purchase process (e.g., Sassenberg et al 2022 ). This is not limited to products but includes issues related to perceived images and positive or negative reactions to what consumers see.…”
Section: Content Analysismentioning
confidence: 99%